Distributions and relationships of virio- and picoplankton in the epi-, meso- and bathypelagic zones of the Amundsen Sea, West Antarctica during the austral summer - Han, Meiaoxue; Luo, Guangfu; He, Jianfeng; Liang, Yantao; Chen, Xuechao; Liu, Gang; Su, Yue; Ge, Fuyue; Yu, Hao; Zhao, Jun; Hao, Qiang; Shao, Hongbing; et al. (Frontiers in Microbiology, 2022)
Virioplankton and picoplankton are the most abundant marine biological entities on earth and mediate biogeochemical cycles in the Southern Ocean. However, understanding of their distribution and relationships with environmental factors is lacking. Here we report on their distribution and relationships with environmental factors at 48 stations from 112.5° to 150°W and 67° to 75.5°S in the Amundsen Sea of West Antarctica. The epipelagic stations were grouped into four clusters based on the virio- and picoplankton composition and abundance. Clusters three and four, which were associated with the ice-edge blooms in the coastal and Amundsen Sea Polynya (ASP) areas, had high abundances of autotrophic picoeukaryotes; this resulted in subsequent high abundances of heterotrophic prokaryotes and viruses. Cluster two stations were in open oceanic areas, where the abundances of autotrophic and heterotrophic picoplankton were low. Cluster one stations were located between the areas of blooms and the oceanic areas, which had a low abundance of heterotrophic prokaryotes and picoeukaryotes and a high abundance of virioplankton. The abundance of viruses was significantly correlated with the abundances of autotrophic picoeukaryotes and Chl-a concentration in oceanic areas, although this reflected a time-lag with autotrophic picoeukaryote and heterotrophic prokaryotes abundances in ice-edge bloom areas. The upwelling of Circumpolar Deep Water (CDW) might have induced the high abundance of autotrophic picoeukaryotes in the epipelagic zone, and the sinking particulate organic carbon (POC) might have induced the high abundance of heterotrophic prokaryotes and virioplankton in the meso- and bathypelagic zones. This study shows that the summer distribution of virio- and picoplankton in the Amundsen Sea of West Antarctica was mainly controlled by upwelling of the CDW and the timing of ice-edge blooms.